The connections between mussel watch for potentially toxic metals and nexus seafood-water-energy - Yap, Chee Kong; Okamura, Hideo; Horie, Yoshifumi; Ong, Meng Chuan; Setyawan, Ahmad Dwi; Zakaly, Hesham MH; Nulit, Rosimah; Syazwan, Wan Mohd; Kumar, Krishnan; Cheng, Wan Hee; Saleem, Muhammad; Naji, Abolfazl; et al. (SciRes Literature LLC, 2023)
The previous assessment intends to support the inaugural International Mussel Watch program's use of marine mussels as biomonitors of potentially toxic metals in aquacultural areas has been considered of low novelty even though it is a necessary biomonitoring. When it is looked into the connections between Mussel Watch and Nexus seafood-water-energy, the questions can be raised up because there is apparently no such discussion in the literature. Therefore, the objective of this review is to discuss the connections between Mussel Watch for potentially toxic metals and Nexus seafood-water-energy, based on the topic reported in the literature separately. The current short review can act as a springboard for additional insights to offer fresh perspectives and original suggestions on using marine mussels more effectively in biomonitoring investigations in connections to Nexus seafood-water-energy. Nowadays, the biomonitoring by using Mussel Watch has remained effective and sustainable which further highlighted their importance in pollution monitoring. The likelihood of improved and wider-ranging molluscan uses in environmental monitoring in the future is almost inevitable. However, more research is still needed to address the rising demand in line with sustainable, attainable United Nation Sustainable Development Goals (‘‘Responsible consumption and production’’, and ‘Good Health and Well-beings’). This is surely a major player in the Nexus’s seafood in cycle with water and energy that should be addressed in future biomonitoring studies.